Atomic-scale study of type-II Dirac semimetal PtTe2 surface. (1st October 2022) - Casado Aguilar, Pablo; Calleja, Fabian; Kuo, Chia-Nung; Lue, Chin Shan; Ghosh, Barun; Agarwal, Amit; Politano, Antonio; Vázquez de Parga, Amadeo L; Miranda, Rodolfo; Silva-Guillén, Jose Angel; Garnica, Manuela
Abstract: Dirac semimetals (DSM) host linear bulk bands and topologically protected surface states, giving rise to exotic and robust properties. Platinum ditelluride (PtTe2 ) belongs to this interesting group of topological materials. Here, we employ scanning tunneling microscopy (STM) in combination with first-principles calculations to visualize and identify the native defects at the surface of a freshly cleaved PtTe2 crystal. Around these defects, short-wavelength electron density oscillations are observed. Fourier transform analysis of the energy-dependent quasiparticle interference patterns is in good agreement with our calculated joint density of states, demonstrating the singular properties of the surface of this type-II DSM. Our results evidence the power of STM in understanding the surface of topological materials.